Identifying the parental figures of children who enter care: The pros and cons of different data linkage methods using Welsh datasets - Warner, Nell; Hodges, Helen Ruth; Scourfield, Jonathan; Cannings-John, Rebecca (International Journal of Population Data Science, 2026)
Introduction Research on the parental figures of children who receive social care services is important, but there are challenges identifying parental figures, particularly fathers, from administrative data in some countries. Objective This paper compares methods for linking to parental figures using different datasets. Methods Children who entered out-of-home care in Wales between 2011 and 2019 were identified from the Looked After Children dataset for Wales (LACW). Those with Anonymous Linking Fields (ALFs) (n=10,679) were linked to different datasets to identify parental figures. The Children and Family Court Advisory and Support Service (Cafcass Cymru) dataset was used to identify parental figures involved in public and private law cases. The Welsh Demographic Service Dataset (WDSD) was used to identify parental figures resident with children before care entry and the National Community Child Health Database (NCCHD) was used to identify biological mothers. The 2011 and 2021 Censuses were used to identify if children were resident with parental figures on Census dates. Descriptive statistics were used to compare linkage rates to female and male parental figures across different datasets, the consistency of linkage and potential biases. Results NCCHD identified female parental figures for 86.9% of the children with an ALF. WDSD identified female parental figures for 71.6% and male parental figures for 42.5%, while Cafcass Cymru data identified female parental figures for 53.9% and male parental figures for 44.0%. Response rates to the 2011 and 2021 Censuses were lower than for the general population, limiting their use. Conclusion NCCHD is useful for identifying biological mothers. WDSD and Cafcass Cymru can both identify limited numbers of male parental figures, but the choice of linkage method would depend on the research questions to be answered.